2022
DOI: 10.1101/2022.08.23.504566
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Murine cytomegalovirus downregulates ERAAP & induces an unconventional T cell response to self

Abstract: The endoplasmic reticulum aminopeptidase associated with antigen presentation (ERAAP) plays a crucial role in shaping the peptide-MHC I repertoire and maintaining immune surveillance. While murine cytomegalovirus (MCMV) has multiple strategies for manipulating the antigen processing pathway to evade immune responses, the host has also developed ways to counter viral immune evasion. In this study, we found that MCMV modulates ERAAP and induces an IFN-gamma; producing CD8+ T cell effector response that targets u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 71 publications
0
7
0
Order By: Relevance
“…ERAAP dsRed is expressed and properly localized to the ER Our lab recently described that cells infected with MCMV express low levels of ERAAP 16 . Through this work, we became interested in identifying the cellular pathways that regulate ERAAP protein levels in cells under normal conditions and determine whether these pathways could be targeted during viral infection.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…ERAAP dsRed is expressed and properly localized to the ER Our lab recently described that cells infected with MCMV express low levels of ERAAP 16 . Through this work, we became interested in identifying the cellular pathways that regulate ERAAP protein levels in cells under normal conditions and determine whether these pathways could be targeted during viral infection.…”
Section: Resultsmentioning
confidence: 99%
“…To avoid detection by CD8 + T-cells, viruses have evolved a myriad of immune evasion mechanisms aimed at preventing the presentation of antigenic peptides 2,13 . Interfering with ERAAP likely represents another one of these strategies as illustrated by HCMV, and likely MCMV [14][15][16] . Furthermore, a recent study by Stamatakis, et al, showed that ERAP generates potentially immunogenic SARS-CoV-2 S-derived peptides predicted to bind MHC 37 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations